Alcohol consumption habits, environments and consequences in Lithuania - Karpuškienė, Vita; Rastenienė, Aušrytė; Liepuonius, Arvydas (Socialinė teorija, empirija, politika ir praktika, 2019)
[full article and abstract in Lithuanian; abstract in English]Excessive consumption of alcoholic beverages is a very sensitive issue for the Lithuanian society. The World Health Organization and the European Union Commission are reporting data of high concern – Lithuania is predominantly the country with the highest rates of alcoholism. The government has adopted amendments to the law from 2018 to 2020 which restrict trade time, legal age of purchasing and drinking alcohol, and alcohol advertising. This regulation applies to all people, regardless of consumer behavior. For long-term results, it is expedient to supplement these restrictive provisions with policy measures that motivate a reduction in alcohol consumption. Therefore, it is necessary to study the habits, the environment and the causes of alcohol consumption.This article presents the results of a study conducted by scientists from the Faculty of Economics of Vilnius University (VU) and representatives of the Lithuanian Confederation of Business (LVK) in December 2016. The purpose of the study is to identify the groups of alcohol beverage users and investigate their consumption behavior. The presented insights delve into three aspects of alcohol consumption: 1) Alcohol consumption and frequency; 2) Consumption habits and conditions; 3) Consequences of consumption.The findings of the survey are compared with the published data of other institutions. The survey analysis revealed that a half of all moderate alcohol consumers drink less than one quarter (23%) of the total one week alcohol volume, while 10% of the most consuming respondents drink more than one third (37%). The patterns and environments of the excluded groups vary, but alcohol is mostly used in a closed home environment with friends, relatives and collaborators.
Keywords: SAV; low risk; binge drinking; heavy episodic drinking